Analysis of The Relationship among Macroeconomics, Monetary and Income Inequality - Abdulrahman Taresh A.; Dyah Wulan Sari; Rudi Purwono (Economics Development Analysis Journal, 2020)
Income inequality in Indonesia remains a controversial issue in the context of Indonesian macroeconomic condition that is evolving in output and government spending, and its increase in consumption accompanied by inflation and slowing of bank credit. The purpose of this study is to investigate the relationship among macroeconomics, monetary and income inequality through a broad theoretical model by adopting a panel Structural Vector Auto-regression (SVAR) model to get more sample size during the period 2005-2018 at 33 provinces in Indonesia. The main results indicate that the variables of output and inflation have positive relationships. The relationship between output and income inequality is also significantly correlated, and those results supported by Kuznets's theory reveal that the relationship between economic growth and income inequality is positive in the short term. The relationship between inflation and income inequality is positive as well in Indonesia. This result is by the fact that low-income families are considered more vulnerable to inflation. The impact of non-food consumption shocks increases income inequality, while Indonesian government spending and bank credit shocks reduce income inequality. Then the response of savings and bank credit to the shock of income inequality is positive.